A bibliography of business and economic forecasting - Fildes, Robert; Dews, David; Howell, Syd.; Facts on File, Inc. (New York, N.Y. : Facts on File, Inc., 1981)
This bibliography contains over 4,000 items, journal articles and books, collected from a search of some thirty journals over the period 1971-1978, together with important references published earlier.
usc 29/10/2021
Ref.
Keywords: Business forecasting; Economic forecasting